Estudos geoquímicos e físico-químicos de alguns tipos de petróleos intemperizados com foco em problemas ambientais - Rainha, Karla Pereira (2020)
Oil exposed to the environment undergoes transformations through complex The oil exposed to the environment triggers a series of impacts to the biogeochemical in to cycles of the exposed ecosystem. Oil weathering is the set of physical, chemical and biolo